2017
DOI: 10.1021/acs.analchem.6b03510
|View full text |Cite
|
Sign up to set email alerts
|

cybLuc: An Effective Aminoluciferin Derivative for Deep Bioluminescence Imaging

Abstract: To enhance the efficiency of firefly luciferase/luciferin bioluminescence imaging, a series of N-cycloalkylaminoluciferins (cyaLucs) were developed by introducing lipophilic N-cycloalkylated substitutions. The experimental results demonstrate that these cyaLucs are effective substrates for native firefly luciferase (Fluc) and can produce elevated bioluminescent signals in vitro, in cellulo, and in vivo. It should be noted that, in animal studies, N-cyclobutylaminoluciferin (cybLuc) at 10 μM (0.1 mL), which is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
2

Year Published

2017
2017
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(25 citation statements)
references
References 41 publications
0
23
0
2
Order By: Relevance
“…This demonstrated that the total light emission and the optimization of imaging conditions and parameters play an important role in the ultimate sensitivity for BLI in vivo. For specific applications in brain that do not require the high resolution provided by NIR-emitting substrates, alternative D-luciferin analogs that produce increased signal have recently been described 36 .…”
Section: Discussionmentioning
confidence: 99%
“…This demonstrated that the total light emission and the optimization of imaging conditions and parameters play an important role in the ultimate sensitivity for BLI in vivo. For specific applications in brain that do not require the high resolution provided by NIR-emitting substrates, alternative D-luciferin analogs that produce increased signal have recently been described 36 .…”
Section: Discussionmentioning
confidence: 99%
“…12,13 Recently, compound 8 and the HCl salt of 5 have shown brighter emission than LH2 at low substrate concentrations. 9,14 Luciferase mutants have also been engineered to give brighter light for some analogues 11,15 including compound 4 under sub-saturating conditions. 16 In 2014, we reported a extended analogue of luciferin infraluciferin (9, iLH2) that exhibited nIR bioluminescence ( max = 706 nm).…”
Section: Methodsmentioning
confidence: 99%
“…Entlang dieser Argumentationslinie wurden die Aminoderivate des Glühwürmchen‐Luciferins ( 2 in Schema ) kürzlich als potenzielle bioinspirierte Emitter von rotem Licht vorgeschlagen . Obwohl das Potenzial solcher Varianten für die Tiefengewebe‐Bildgebung bereits gezeigt wurde, bleibt die zugrundeliegende Photochemie unklar (detaillierte Informationen zu beschriebenen Aminoluciferinen finden sich in den Hintergrundinformationen, SI). Kürzlich beobachteten wir zufällig, dass Kristalle von N , N ‐Dimethylaminoluciferin 3 (Diagramm 1) ihre Fluoreszenzemission stark erhöhen nachdem sie blauem LED‐Licht ausgesetzt wurden.…”
Section: Methodsunclassified